Quantifying individual heterogeneity and its influence on life‐history trajectories: different methods for different questions and contexts. Issue 5 (26th October 2017) - Hamel, Sandra; Gaillard, Jean‐Michel; Douhard, Mathieu; Festa‐Bianchet, Marco; Pelletier, Fanie; Yoccoz, Nigel G.
Abstract : Heterogeneity among individuals influences the life‐history trajectories we observe at the population level because viability selection, selective immigration and emigration processes, and ontogeny change the proportion of individuals with specific trait values with increasing age. Here, we review the two main approaches that have been proposed to account for these processes in life‐history trajectories, contrasting how they quantify ontogeny and selection, and proposing ways to overcome some of their limitations. Nearly all existing approaches to model individual heterogeneity assume either a single normal distribution or a priori known groups of individuals. Ontogenetic processes, however, can vary across individuals through variation in life‐history tactics. We show the usefulness of describing ontogenetic processes by modelling trajectories with a mixture model that focuses on heterogeneity in life‐history tactics. Additionally, most methods examine individual heterogeneity in a single trait, ignoring potential correlations among multiple traits caused by latent common sources of individual heterogeneity. We illustrate the value of using a joint modelling approach to assess the presence of a shared latent correlation and its influence on life‐history trajectories. We contrast the strengths and limitations of different methods for different research questions, and we exemplify the differences among methods using empirical data from long‐term studies of ungulates.